The Assessment of Animal Welfare Implementation in Poultry Slaughter House in Kisaran City Asahan District - Ridho Akbar Yuandi; Mulyadi Adam; Sri Wahyuni (Jurnal Medika Veterinaria, 2022)
This study aimed to assess the aspect of animal welfare in poultry slaughter house at Bakti market, Kartini market, and Diponegoro market in Kisaran city Asahan District North Sumatra Province. This research was conducted using direct observation and interview methods using a structured questionnaire based on animal welfare aspects. There were three aspects assesed in this study, including transportation aspects, shelter aspects and slaughter aspects. The results of the studies showed that some of the animal welfare aspects have been applied positively in poultry slaughter house in Kisaran City. However, improvements are required to be implemented in some poultry slaughter house in this area